Plant Cell Walls 2001
DOI: 10.1007/978-94-010-0668-2_16
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics and cell wall biosynthesis in loblolly pine

Abstract: Loblolly pine (Pinus taeda L.) is the most widely planted tree species in the USA and an important tree in commercial forestry world-wide. The large genome size and long generation time of this species present obstacles to both breeding and molecular genetic analysis. Gene discovery by partial DNA sequence determination of cDNA clones is an effective means of building a knowledge base for molecular investigations of mechanisms governing aspects of pine growth and development, including the commercially relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
71
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 43 publications
(46 reference statements)
4
71
1
3
Order By: Relevance
“…Total RNA was extracted from linkage analysis because recombination estimators are still valid when distortion is observed at only one locus of a from ‫5ف‬ g of ground tissue following the protocol of Chang et al (1993). Double-stranded cDNA was prepared using the linked pair of loci (Bailey 1961;Ott 1991). ESTP markers were added to the existing segregation data ( Jermstad et al Universal RiboClone cDNA Synthesis System (Promega, Madison, WI), filtered through a Sephacryl S-400 column, ligated 1998) and the linkage analysis was repeated.…”
Section: Douglas Fir Est and Sts Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted from linkage analysis because recombination estimators are still valid when distortion is observed at only one locus of a from ‫5ف‬ g of ground tissue following the protocol of Chang et al (1993). Double-stranded cDNA was prepared using the linked pair of loci (Bailey 1961;Ott 1991). ESTP markers were added to the existing segregation data ( Jermstad et al Universal RiboClone cDNA Synthesis System (Promega, Madison, WI), filtered through a Sephacryl S-400 column, ligated 1998) and the linkage analysis was repeated.…”
Section: Douglas Fir Est and Sts Markersmentioning
confidence: 99%
“…To overcome this problem a computational apspecies, loblolly pine has rich genetic resources, welldeveloped genetic and QTL maps (Sewell et al 1999; proach was used to identify Douglas fir ESTs with high homology, and putative orthology, to ESTPs mapped in Brown et al 2001Brown et al , 2003Temesgen et al 2001), and expressed sequence tag (EST) databases (Allona et al loblolly pine. A similar approach was used in recent comparative mapping studies between tomato, potato, 1998; Whetten et al 2001;Kirst et al 2003). Douglas fir (Pseudotsuga menziesii [Mirb.]…”
mentioning
confidence: 99%
“…Currently, Pinus taeda is the only conifer species for which extensive sequence information is available (http://pine.ccgb.umn.edu). Microarray analysis has previously been used for identifying genes involved in cell wall biosynthesis during xylogenesis in P. taeda (Whetten et al, 2001). Recently, we showed that arrays from P. taeda can be used for studying gene expression in Picea abies and Pinus sylvestris (van Zyl et al, 2002a(van Zyl et al, , 2002bStasolla et al, 2003).…”
mentioning
confidence: 99%
“…There has been extensive research on genes expressed in wood, identifying key genes in the process of xylogenesis (such as the myb transcription factor, phenylalanine ammonia lyase, glycine hydroxymethyltransferase) and contributing to building an accessible database of genes involved in the genetic control of the properties of wood, including metabolic routes (Whetten et al, 2001). However, the process of wood formation is still not well characterized.…”
Section: Introductionmentioning
confidence: 99%